2021
DOI: 10.1007/s12204-021-2299-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Printing and WebGL-Based 3D Visualisation Technology in Imaging Teaching of Ankle Joints

Abstract: With the rapid development of medical technology, 3D printing technology with realistic representation can perfectly display static human anatomy, while 3D visualisation technology based on Web Graphics Library (WebGL) can promote the rigid replication characteristics of traditional teaching models and express the dynamic spatial relationship between different anatomical structures. Medical students traditionally have less cognition of ankle ligament sprains. In this study, computed tomography (CT) and magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Online remote 3D visualization is also widely used in the field of medical teaching. 21,27,28 Tan et al 29 showed that not only are students enabled to observe the construction of a human skeleton anatomy model more intuitively to stimulate their interest in learning, but also teacher lesson preparation efficiency and teaching effect are improved by constructing a new teaching platform of a Web-based 3D human skeleton anatomy model. However, these methods are seldom used in the field of medical tele-diagnosis, which requires high interactive speed and 3D image reconstruction quality.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Online remote 3D visualization is also widely used in the field of medical teaching. 21,27,28 Tan et al 29 showed that not only are students enabled to observe the construction of a human skeleton anatomy model more intuitively to stimulate their interest in learning, but also teacher lesson preparation efficiency and teaching effect are improved by constructing a new teaching platform of a Web-based 3D human skeleton anatomy model. However, these methods are seldom used in the field of medical tele-diagnosis, which requires high interactive speed and 3D image reconstruction quality.…”
Section: Related Workmentioning
confidence: 99%
“…For example, medical data or images are transmitted on the Internet to realize online remote 3D visualization especially when mobile devices are widely used in medical. [19][20][21] In fact, online remote 3D visualization has long been widely used in geometric information systems. 22,23 Currently, online terrain visualization has become an important part of many 3D online games, mapping applications, earth visualization systems, and navigation systems.…”
Section: Related Workmentioning
confidence: 99%
“…[1][2][3] LM is also known as the metal with melting point below 300 °C. [4,5] Mercury (Hg), as one kind of common LMs, is used in thermometers. However, mercury is volatile and toxic, which limits its use.…”
mentioning
confidence: 99%